Prevalence of the relative age effect among high-performance, university student-athletes, versus an age-matched student cohort - Dube, S.; Grobbelaar, H. (South African Journal of Sports Medicine, 2022)
Background: Relative age effect (RAE) refers to the overrepresentation of athletes born earlier in the calendar year covering a specific sport. The RAE is especially prevalent in youth sports but often persists into senior competitive levels.